The Effect of Fashion FOMO (Fear of Missing Out) on Purchase Decisions of the Fast Fashion Brand Uniqlo in Semarang City with Minimalist Wardrobes as a Moderating Variable - Ardella Tasya Nismona; Agung Sedayu; Aries Setiawan; Tito Aditya Perdana (Proceeding of the International Conference on Management, Entrepreneurship, and Business, 2025)
The phenomenon of fashion FOMO (fear of missing out) exerts a significant influence on fashion consumption behavior, particularly among the demographic from late adolescence to young adulthood. The fear of missing trends can lead individuals to make impulsive purchases. In contrast, the Minimalist Wardrobe concept promotes a conscious lifestyle that emphasizes functional and sustainable clothing choices. The objective of this study is to examine the influence of Fashion FoMO on purchasing decisions and to assess the role of a Minimalist Wardrobe as a moderating variable. A quantitative approach was employed, utilizing purposive sampling to collect data through surveys administered to respondents residing in Semarang City. The data were analyzed using the Structural Equation Modeling (SEM) method with SmartPLS software. The results show that Fashion FoMO has a significant and positive influence on purchasing decisions for UNIQLO products. Meanwhile, the Minimalist Wardrobe shows an insignificant effect. These findings suggest that purchasing decisions are more strongly driven by emotional pressure from FoMO than by minimalist lifestyle considerations.